Cost-Effectiveness of Colonoscopy-Based Colorectal Cancer Screening in Childhood Cancer Survivors. (13th April 2019) - Gini, Andrea; Meester, Reinier G S; Keshavarz, Homa; Oeffinger, Kevin C; Ahmed, Sameera; Hodgson, David C; Lansdorp-Vogelaar, Iris
Abstract: Background: Childhood cancer survivors (CCS) are at increased risk of developing colorectal cancer (CRC) compared to the general population, especially those previously exposed to abdominal or pelvic radiation therapy (APRT). However, the benefits and costs of CRC screening in CCS are unclear. In this study, we evaluated the cost-effectiveness of early-initiated colonoscopy screening in CCS. Methods: We adjusted a previously validated model of CRC screening in the US population (MISCAN-Colon) to reflect CRC and other-cause mortality risk in CCS. We evaluated 91 colonoscopy screening strategies varying in screening interval, age to start, and age to stop screening for all CCS combined and for those treated with or without APRT. Primary outcomes were CRC deaths averted (compared to no screening) and incremental cost-effectiveness ratios (ICERs). A willingness-to-pay threshold of 100 000 per life-years gained (LYG) was used to determine the optimal screening strategy. Results: Compared to no screening, the US Preventive Services Task Force's average risk screening schedule prevented up to 73.2% of CRC deaths in CCS. The optimal strategy of screening every 10 years from age 40 to 60 years averted 79.2% of deaths, with ICER of 67 000/LYG. Among CCS treated with APRT, colonoscopy every 10 years from age 35 to 65 years was optimal (CRC deaths averted: 82.3%; ICER: 92 000/LYG), whereas among those not previously treated with APRT, screening from age 45 to 55 years every 10 years was optimal (CRC deaths averted: 72.7%; ICER: 57 000/LYG). Conclusions: Early initiation of colonoscopy screening for CCS is cost-effective, especially among those treated with APRT.